New record of Melanophryniscus biancae bornschein, baldo, pie, firkowski, ribeiro & corrêa, 2015 (anura, bufonidae) from Paraná, Brazil, with comments on its phytotelm-breeding ecology - Nadaline, Júnior (2019)
We report Melanophryniscus biancae Baldo, Pie, Firkowski, Ribeiro & Corrêa, 2015 from Araçatuba, Tijucas do Sul, Paraná, Brazil at 1,615-1,645 m altitude, the first record from the state of Paraná. On 8 January 2018 we heard individuals calling during the day in the leaves of Paepalanthus planifolius (Bong.) Körn. where eggs, tadpoles, and three adults were collected. This species was recently described from two upland marshes (1,310-1,465 m altitude) in northeastern Santa Catarina, where it was found at night breeding in water tanks of Eriocaulon ligulatum (Vell.) L.B.Sm. Included here are new data on this species’ habitat, activity period, plant species used for oviposition, and the first female measurements.